(untitled) (Journal of Entrepreneurship and Business, 2024)
Increased digitalization is one of the tailwinds expected to impact the Islamic Financial Services Industry (IFSI), including the takaful industry, which is growing at up to 5.2% globally. Despite the increasing penetration of digital technologies, the participation rate in online takaful remains disproportionately low. Hence, a call for a digital platform is seen as vital in the current economic situation to further reach out. This research suggests an integrated model of e-takaful participation readiness (ETPR) and empirically tests the model. Furthermore, this study opts for primary data via a structured online survey adapted from previous studies using a purposive sampling technique. Partial Least Square - Structural Equation Modelling (PLS-SEM) is the main statistical technique used in this study. Based on the perspective of user acceptance of information technology, the current research significantly expands on factors influencing e-takaful participation readiness among 395 individuals such as religiosity, attitude, and takaful literacy. Past studies have visited the topic of e-banking readiness, but limited studies focused on its relation to the e-takaful area. This study is a pioneer in examining consumer participation readiness toward e-takaful services particularly during the digital shifting process due to pandemic. The results supported the measurement model’s prediction that each research measure’s reliability and validity requirements were met. All the proposed hypotheses were found to be significant and accepted. The findings of this study suggest takaful operators in Malaysia to critically devise their new penetration strategies and focus on giving extra value to induce takaful literacy and make room for improvement in product penetration to the target segments by understanding the factors contributing to this phenomenon. This is crucial for policymakers, takaful operators, and other industry stakeholders to develop strategies that encourage greater adoption of online participation.